367 Effect of waiting time from pathological diagnosis to definitive concurrent chemoradiation (CCRT) for cervical cancer on overall survival. (13th November 2020) - Yeo, H; Noh, K; Lee, Y; Choi, CH; Kim, T; Lee, J; Kim, B; Bae, D; Cho, W; Park, W
Abstract : Objective: This study aimed to evaluate the effect of waiting time, from diagnosis to initiation of definitive concurrent chemoradiation (CCRT), on overall survival in cervical cancer patients. Methods: Patients with cervical cancer who were diagnosed with definitive CCRT between 2000 and 2017 were retrospectively reviewed. Time from pathological diagnosis to definitive CCRT was analyzed both as a continuous variable (per day) and as a categorical variable in 2 groups (Group 1 ≤ median, Group 2 > median). Patients with a waiting time of more than 60 days were excluded. Results: The median waiting time was 14 days (0–60). There were differences between Group 1 and Group 2 in age and type of chemotherapy. However, no significant difference was found in the FIGO stage, cell type, or the number of cycles of chemotherapy received during CCRT. A longer waiting time was associated with poorer overall survival on the Kaplan-Meir curve (Group 1 vs. Group 2, P = 0.042). On multivariate analysis, intervals as either a continuous variable (HR; 1. 023, 95% CI; 1.006–1.040, P = 0.007) or a categorical variable (HR; 1.513, 95% CI; 1.073–2.134, P = 0.018), FIGO stage, cell type, and the number of cycles of chemotherapy received during CCRT were significant independent prognostic factors for overall survival. Patients were divided into two groups based on the median waiting time. Conclusions: A longer waiting time from pathological diagnosis to definitive CCRT was associated with worse overall survival. Our findings suggest that an effort to minimize waiting times should be made in cervical cancer patients who are candidates for CCRT.